The Moderating Role of Transformational Leadership in the Influence of Work-Life Balance, Work Environment, and Competence on Employee Performance - Hartuti; -, Agustinus Setyawan (Jurnal Manajemen (Edisi Elektronik), 2025)
This study investigates the effects of work-life balance, work environment and competence on employee performance, while also examining transformational leadership as a moderator. Data were collected through questionnaires distributed to 300 Internal Government Oversight Personnel (APIP) at the Regional Inspectorates of Riau Islands Province, yielding 189 valid responses. Using SmartPLS 3.0 and the PLS-SEM method, the analysis revealed that work-life balance, competence, and transformational leadership have a positive and significant impact on employee performance, whereas the work environment does not. Additionally, transformational leadership does not moderate the relationship between either competence or work environment and performance. Practically, the study suggests that enhancing technical skills and professional ethics is more beneficial than improving physical workspace conditions. Given the high competence and experience of employees, transformational leadership may be less effective, and flexible leadership styles (e.g., coaching or mentoring) are recommended. Organizations should also adopt supportive work-life balance policies, such as flexible hours, to optimize employee performance.